2017
DOI: 10.1111/ppe.12409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Contributors to Low‐grade Inflammation in Three U.S. Populations of Reproductive Age Women

Abstract: Background: Inflammation, measured by high-sensitivity C-reactive protein (hsCRP), is linked to adverse reproductive outcomes. However, prevalence and predictors of low-grade inflammation are poorly understood among reproductive age women. Therefore, the current aim was to characterize: (i) the prevalence of elevated hsCRP and (ii) whether the association of various demographic, anthropometric, life style, and metabolic characteristics with higher hsCRP varies across populations of reproductive age women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Inflammation caused by organic diseases, such as endometriosis, polycystic ovary syndrome (PCOS) or obesity, is a well-known cause of infertility ( Cho et al, 2008 ; Çakıroğlu et al, 2016 ) . However, Sjaarda et al (2018) tested the inflammatory status by high-sensitive C-reactive protein (hs-CRP) and found that low-grade inflammation is very common (20-40%) in reproductive-age women, including normal-weight women. Apart from hs-CRP, systemic inflammatory status could be assessed by NLR, MLR, and PLR ( Mertoglu et al, 2019 ; Madendag et al, 2018 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation caused by organic diseases, such as endometriosis, polycystic ovary syndrome (PCOS) or obesity, is a well-known cause of infertility ( Cho et al, 2008 ; Çakıroğlu et al, 2016 ) . However, Sjaarda et al (2018) tested the inflammatory status by high-sensitive C-reactive protein (hs-CRP) and found that low-grade inflammation is very common (20-40%) in reproductive-age women, including normal-weight women. Apart from hs-CRP, systemic inflammatory status could be assessed by NLR, MLR, and PLR ( Mertoglu et al, 2019 ; Madendag et al, 2018 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Using PASS 16 software (NCSS, LLC, Kaysville, Utah), power calculations for the sample of 781 patients indicated the study would have 80% power to detect a RR for live birth of 0.59 for hs-CRP ≥3.0, given a 5% type I error rate for false-positive conclusions (two-sided alpha = 0.05) and an R 2 of 0.2 for the degree of correlation between the hs-CRP levels and the other covariates. For these calculations, we assumed a 25% live birth rate among women with normal hs-CRP (<3.0 mg/L) corresponding to the birth rate observed in the AMIGOS trial and assumed a 30% prevalence of elevated hs-CRP given reports of low-grade inflammation in 20%–40% of reproductive age women ( 3 ). This study received approval from the University of Oklahoma Health Science Center’s Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…No readily identifiable cause is found for 15%–30% of couples following a standard evaluation, leading to a diagnosis of unexplained infertility ( 1 ). Chronic inflammation, frequently assessed by serum high-sensitivity C-reactive protein (hs-CRP) levels, has been linked to adverse reproductive outcomes, including reduced fecundability, recurrent miscarriage, and recurrent in vitro fertilization (IVF) failures ( 2 , 3 ). The hs-CRP is an acute phase reactant protein released from the liver and serves as a marker to identify inflammation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SUPPORT FERTILITY & STERILITY Ò e103 MATERIALS AND METHODS: Of the 900 AMIGOS participants, 778 were available for analysis after excluding patients with hsCRP levels R10 indicative of infection, ectopic pregnancies and those missing pregnancy outcome or baseline hs-CRP serum measures. Hs-CRP concentration was evaluated using two definitions: first by hs-CRP categories of < 2mg/L and 2 -9.9 mg/L as previously defined in the literature, and second, by tertiles (tertile 1 % 0.725 mg/L, tertile 2 0.725 to 2.42 mg/L, and tertile 3 > 2.42 mg/ L) 1 . Risk ratios (RR) and 95% confidence intervals for the outcomes of live birth, clinical pregnancy, and pregnancy loss were estimated using modified Poisson regression models with robust standard errors.Adjustment for covariates were examined in multivariable models.…”
mentioning
confidence: 99%